UPAYA PENGEMBANGAN USAHA PETERNAKAN SAPI PERAH RAKYAT DI KABUPATEN KLATEN - ERLYANA WIDA R (Universitas Sebelas Maret, 2009)
Klaten regency represent one of regency in Central Java province have big enough dairy cattle population. During six the last year shown that decreasing the amount of population and productivity.